Pengaruh Model Pembelajaran Talking Stick Terhadap Hasil Belajar Peserta Didik di SMKN 1 Depok - Anita Wijayanti; Kanaria Herwati; Indra Suyahya (Neolectura, 2021)
The purpose of this study was to determine the effect of the talking stick learning model on student learning outcomes at SMKN 1 Depok. The population of this study were students of class XI SMKN 1 Depok. The number of samples as many as 73 students were taken using a saturated sample. The research method used is an experimental method using observation collection, learning outcomes tests and documentation and data analysis techniques descriptive statistical analysis, normality test, homogeneity test and hypothesis. Based on this research, it is expected that student learning outcomes can be improved using the talking stick learning model. The results of the research that have been carried out based on the results of descriptive statistical analysis obtained the average value of the two groups, the experimental group taught using the talking stick learning model was 80.01 and the control group was taught using the conventional learning model was 54.47. The results of the t-test of student learning outcomes using the learning outcomes test instrument obtained tcount = 11.261 while ttable = 1.994 (dk = 71). Thus, tcount > ttable is 11.261>1.994. This means that there is an influence of the talking stick learning model on the learning outcomes of students at SMKN 1 Depok.